2010
DOI: 10.1097/wnr.0b013e3283383df5
|View full text |Cite
|
Sign up to set email alerts
|

Sweet taste-induced analgesia: an fMRI study

Abstract: We investigated the brain activation associated with sweet taste-induced analgesia by 3-T functional magnetic resonance imaging, the mechanism of which is considered to involve the central nervous system. After 12 healthy individuals ingested tasteless gelatin (nonsweet condition) or sweet glucose (sweet condition) in a magnetic resonance imaging scanning gantry, the cold pressor test was applied to their medial forearm. Under both conditions, the cold pressor test robustly activated the pain-related neural ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 26 publications
1
36
0
Order By: Relevance
“…In fact, there is considerable evidence that sucrose or other hedonic substances can provide analgesia, including inhibition of spontaneous behaviors in the formalin test in rodents and reduction of the response to acute painful stimuli in psychophysical studies in humans [4; 16; 21; 33]. Therefore, in the next experiment we asked whether the enhanced sucrose consumption that we observed was, in fact, driven by DPI-induced pain.…”
Section: Resultsmentioning
confidence: 87%
“…In fact, there is considerable evidence that sucrose or other hedonic substances can provide analgesia, including inhibition of spontaneous behaviors in the formalin test in rodents and reduction of the response to acute painful stimuli in psychophysical studies in humans [4; 16; 21; 33]. Therefore, in the next experiment we asked whether the enhanced sucrose consumption that we observed was, in fact, driven by DPI-induced pain.…”
Section: Resultsmentioning
confidence: 87%
“…However, previous studies reported that sweet taste has an analgesic effect. 1,39 For example, an experimental study showed that holding sucrose in the mouth was significantly associated with a 35% prolongation of children's threshold times compared to holding water in their mouths while undergoing the cold pressor test. 1 Furthermore, sugar is hypothesized to potentially be an addictive substance, and palatable foods high in sugar are often consumed in a way similar to the way drugs are abused.…”
Section: Discussionmentioning
confidence: 99%
“…The histamine level increases in the PP state, and it has been shown to have an analgesic effect via the H3 receptor [8][9][10]. Recently, sweet taste-induced analgesia was demonstrated in humans by doing a functional MRI [11]. The decreased pain sensitivity which is produced by the above phenomena may lead to a decrease in the CVR in the ½ an hours post-prandial state.…”
Section: Discussionmentioning
confidence: 99%